Difference in pacing between time- and distance-based time trials in trained cyclists - Abbiss, C. R.; Thompson, K. G.; Lipski, M.; Meyer, T.; Skorski, S. (International Journal of Sports Physiology and Performance, 2016)
The purpose of this study was to compare the pacing profiles between distance- and duration-based trials of short and long duration. Thirteen trained cyclists completed 2 time-based (6 and 30 min) and 2 distance-based (4 and 20 km) self-paced cycling time trials. Participants were instructed to complete each trial with the highest average power output. Ratings of perceived exertion (RPEs) were measured throughout the trials. Average power output was not different between the 4-km and 6-min trials (324 ± 46 vs 325 ± 45 W; P = .96) or between the 20-km and 30-min trials (271 ± 44 vs 267 ± 38 W; P = .24). Power output was greater on commencement of the distance-based trials when short and long trials were analyzed together. Furthermore, the rate of decline in power output over the 1st 40% of the trial was greater in the 20-km trial than in the 30-min trial (P = .01) but not different between the 4-km and the 6-min trials (P = .13). RPE was greater in the 4-km trial than in the 6-min trial but not different between the 20-km and 30-min trials. These findings indicate that athletes commenced distance-based time trials at relatively higher power outputs than a similar time-based trial. Such findings may result from discrete differences in our ability to judge or predict an exercise endpoint when performing time- and distance-based trials.